Bromodomain proteins IBD1 and IBD2 link histone acetylation to SWR1- and INO80-mediated H2A.Z regulation in Tetrahymena - Jyoti Garg; Alejandro Saettone; Syed Nabeel-Shah; Steven Dang; Abdul Hadi Khalid; Jérémy Loehr; Alexandra Petrova; James D. Burns; Peter Karabatsos; Sherin Shibin; Suzanne Wahab; Sean D. Taverna; et al. (Epigenetics & Chromatin)
Abstract Background INO80 and SWR1 are evolutionarily related ATP-dependent chromatin remodeling complexes that regulate the chromatin occupancy of the histone variant H2A.Z, playing critical roles in transcriptional regulation, genome replication, and DNA repair. While the H2A.Z-related functions of INO80 and SWR1 are well characterized in budding yeast and metazoans, much less is known about their composition and chromatin-targeting mechanisms outside of the Opisthokonts. We previously found that a distinct bromodomain-containing protein, IBD1, is involved in multiple chromatin-related complexes, including the SWR1-complex, in the ciliate protozoan Tetrahymena thermophila. Results Here, we report that a closely related bromodomain-containing protein, IBD2, functions as an acetyl lysine reader module within a putative INO80 complex. Through iterative proteomic analyses, we show that the Tetrahymena INO80 complex retains several conserved subunits found in its yeast and metazoan counterparts. In vitro binding assays reveal that recombinant IBD2 preferentially recognizes acetylated histone H3 tails. Chromatin immunoprecipitation followed by high-throughput sequencing (ChIP-seq) demonstrates that IBD2 is enriched near transcription start sites and promoter regions. Notably, the IBD1 and IBD2 genomic binding profiles strongly correlate with that of H2A.Z (Hv1), supporting their functional association with the SWRI- and INO80-complexes. Conclusions Together, our findings support a model in which H2A.Z chromatin dynamics are modulated by SWR1- and INO80-complexes that are differentially recruited to chromatin via distinct bromodomain proteins that recognize specific histone acetylation marks.